Need Analysis on English Teaching at Mts Nurul Qolbi: Activities and Assessment - Erniyanti Nur Fatahhela Dewi; Mentari; Nindya Hasanah (CV. Eureka Murakabi Abadi, 2023)
The research aims to find out English Classroom activities and assessment based on students’ need analysis and teacher’s perception. The quantitative and qualitative method were conducted in this research to describe the students’ needs. In collecting the data, the researchers applied interview for teacher and questionnaire for the students as the instrument of the research. There were one teacher and 30 students as participants in this research by conducting purposive sampling. The findings showed that researchers can use the topic that they provide to develop materials in needs analysis for the student in language teaching. In addition, assessment activity on the topic of invitation, give instructions and ask permissian was suggested to use feedback from friends. While, making a greeting card topic was suggested to use feedback from the teacher. Hence, showing the existence of a person or thing topic was suggested to use role play.